2007
DOI: 10.1103/physrevd.75.063512
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependence of halo and galaxy bias: Effects in real space

Abstract: We examine the scale dependence of dark matter halo and galaxy clustering on very large scales (0:01 < k h Mpc ÿ1 < 0:15), due to nonlinear effects from dynamics and halo bias. We pursue a two line offensive: high-resolution numerical simulations are used to establish some old and some new results, and an analytic model is developed to understand their origins. Our simulations show: (i) that the z 0 dark matter power spectrum is suppressed relative to linear theory by 5% on scales 0:05 < k h Mpc ÿ1 < 0:075; (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
362
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(381 citation statements)
references
References 87 publications
(169 reference statements)
18
362
1
Order By: Relevance
“…In practice, one often replaces the 2-halo term by the linear two-point correlation, or power spectrum, to reproduce linear theory on large scales. Previous works (Cooray & Sheth 2002;Smith et al 2003Smith et al , 2007Giocoli et al 2010) have shown that halo models provide a good match to numerical simulations, especially at high k, whereas Lagrangian mappings based on the stable clustering ansatz (Peebles 1980) do not fare as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, one often replaces the 2-halo term by the linear two-point correlation, or power spectrum, to reproduce linear theory on large scales. Previous works (Cooray & Sheth 2002;Smith et al 2003Smith et al , 2007Giocoli et al 2010) have shown that halo models provide a good match to numerical simulations, especially at high k, whereas Lagrangian mappings based on the stable clustering ansatz (Peebles 1980) do not fare as well.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to combine perturbation theory and nonlinear halo bias to make the expression above consistent with standard perturbation theory while building a model for the halo power spectrum itself, see Smith et al (2007). Of course, in order to describe the weakly nonlinear regime one can as well replace P L (k) by P pert (k) in Eq.…”
Section: "2-halo" Contributionmentioning
confidence: 99%
“…Even though it is beyond the scope of this paper to discuss the impact of the systematic effects present on the modeling of the quantities mentioned above, we recognize their relevance in extracting accurate information regarding the parameters describing the observed clustering pattern of galaxy clusters (especially using the luminosity power spectrum) from forthcoming galaxy and galaxy cluster surveys such as eROSITA, DES (The Dark Energy Survey Collaboration 2005), or Euclid (Laureijs et al 2011). We notice that the only model that we have explicitly implemented in our analysis makes the assumption that the halo distribution behaves like a Poisson point process, which is a debatable hypothesis (see, e.g., Casas-Miranda et al 2002;Smith et al 2007). With this assumption, the shot-noise correction of the halo power spectrum is represented by subtracting a white noise from the raw power spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the halo distribution n(r; L) is the result of an inhomogeneous Poisson point process. Strictly speaking, a Poisson model cannot properly describe the distribution of galaxy clusters since these objects are subject to the so-called halo exclusion effects (e.g., Porciani & Giavalisco 2002;Tinker et al 2005;Smith et al 2007). This effect arises because halos are treated as disjointed entities that are not allowed to overlap, leading to a correlation function ξ(r) → −1 on scales below the minimum scale probed by the halo catalog (for an ideal sample of spherical halos, this scale equals twice the radius of the smaller halo, e.g., Peebles 1980).…”
Section: Definitionsmentioning
confidence: 99%
“…Following proof-of-concept work (e.g. Blake & Glazebrook 2003;Seo & Eisenstein 2003), it is now apparent that the BAOs are not quite a standard ruler and, furthermore, they can be altered by a range of effects (Seo & Eisenstein 2005Smith et al 2007Smith et al , 2008Angulo et al 2008;Crocce & Scoccimarro 2008;Sánchez et al in press;Seo et al in press). Careful modelling is required to produce accurate predictions for the form of the BAOs and to help devise estimators to exploit these features in order to extract unbiased constraints on the dark energy.…”
Section: Do We Really Need To Go This Far?mentioning
confidence: 99%